Randomized, double‐blind, placebo‐controlled study of safety and efficacy of miltefosine in antihistamine‐resistant chronic spontaneous urticaria. (29th August 2012) - Magerl, M.; Rother, M.; Bieber, T.; Biedermann, T.; Brasch, J.; Dominicus, R.; Hunzelmann, N.; Jakob, T.; Mahler, V.; Popp, G.; Schäkel, K.; Schlingensiepen, R.; et al.
Abstract Background Chronic spontaneous urticaria (CSU), a mast cell‐driven condition, is debilitating, common, and hard to treat. Miltefosine, a lipid raft modulator, can inhibit mast cell responses in vivo. Objective To study the safety and efficacy of systemic miltefosine treatment in CSU patients resistant to standard‐dosed antihistamines. Methods In this investigator‐initiated multicentre, randomized, double‐blind, placebo‐controlled study, CSU patients were treated for 4 weeks with daily doses of up to 150‐mg miltefosine (n = 47) or placebo (n = 26). Disease activity was assessed using the urticaria activity score. Safety and tolerability of miltefosine were also assessed. Results After 4 weeks of treatment, Urticaria Activity Score (UAS7) levels were substantially more reduced in miltefosine‐treated patients (−6.3 vs. −3.5 in placebo‐treated patients; P = 0.05). Also, the number of weals, but not the intensity of pruritus, was significantly reduced in miltefosine‐treated patients vs. placebo‐treated patients (P = 0.02). In general, adverse events were frequent in both groups (miltefosine: 88%, placebo: 65% of patients) but mostly mild to moderate in severity. We did not observe any serious adverse events. Conclusions The results of this study indicate that miltefosine is an effective and safe treatment option for CSU patients who do not respond to standard‐dosed antihistamines.